Respiratory distress in the newborn - an ophthalmologic diagnosis - Maio, Tiago Daniel da Silva (2019)
The presence of a congenital dacryocystocele is rare, the presence of two with nasal extension compromising respiratory function, make this an atypical case that requires immediate action by the ophthalmologist. We present the case of a newborn that during the first hours of life presented respiratory distress. Dacryocystocele resolution and symptomatic improvement were observed after conservative treatment. Keywords: congenital dacryocystocele; newborn; respiratory distress; conservative treatment